1995
DOI: 10.1161/01.cir.91.6.1714
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Muscle Perfusion Pattern

Abstract: Myocardial infarction may cause papillary muscle dysfunction when the blood supply is provided by one rather than two vessels, as is more frequently the case with the posterior rather than the anterior papillary muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(26 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…The increased vulnerability of the posteromedial PM is likely related to its blood supply, which is usually dependent on 1 artery (either the right coronary artery [RCA] or the left circumflex coronary artery [LCX]), whereas the anterolateral PM is supplied by 2 arteries (the left anterior descending coronary artery [LAD] and the LCX). 18 This was further supported by Chinitz et al 14 who demonstrated that in patients with posteromedial PM infarction the LCX was the infarct-related artery in 33% and the RCA in 67%, whereas the LAD was never involved. Conversely, in patients with anterolateral PM infarction, the LAD was the infarct-related artery in 72% of patients, the LCX in 22%, and the RCA in 6%.…”
mentioning
confidence: 74%
“…The increased vulnerability of the posteromedial PM is likely related to its blood supply, which is usually dependent on 1 artery (either the right coronary artery [RCA] or the left circumflex coronary artery [LCX]), whereas the anterolateral PM is supplied by 2 arteries (the left anterior descending coronary artery [LAD] and the LCX). 18 This was further supported by Chinitz et al 14 who demonstrated that in patients with posteromedial PM infarction the LCX was the infarct-related artery in 33% and the RCA in 67%, whereas the LAD was never involved. Conversely, in patients with anterolateral PM infarction, the LAD was the infarct-related artery in 72% of patients, the LCX in 22%, and the RCA in 6%.…”
mentioning
confidence: 74%
“…Contiguous short-axis slices and representative long-axis slices of the LV were obtained 10 minutes after intravenous injection of 0.1 mmol/kg Gd-DTPA (Magnevist, Schering AG, Berlin, Germany). Scan parameters were as follows: repetition time, 4.1 milliseconds; echo time, 1.25 milliseconds; flip angle, 15°; field of view, 350ϫ350 mm; partial echo; matrix, 224ϫ256; and spatial resolution, 1.56ϫ2.24ϫ10 mm 3 reconstructed to 0.68ϫ0.68ϫ5 mm 3 . All images were acquired during breath-hold at end expiration.…”
Section: Mri Protocolmentioning
confidence: 99%
“…On the other hand, the anterior papillary muscle has a dual blood supply from the left anterior descending artery (LAD) and the LCx. 3 …”
mentioning
confidence: 99%
“…This branch of the left circumflex artery feeds the papillary muscles and can be involved in cases of PMR 2 . PMR complicates up to 5% of cases of fatal, acute MI 3 .…”
Section: Discussionmentioning
confidence: 99%